The Effectiveness of BmT Accompanied by Music Therapy for Neurology Patients at Martha Friska Multatuli Hospital - Waruwu, Happy Majesty; Batubara, Junita; Saragih, Ronald Heriko; Lumbangaol, Samsa Tamara (Gondang: Jurnal Seni dan Budaya, 2023)
This research focuses on the application of BmT (Box Music Therapy) as a music therapy medium for treating neurological patients in Martha Friska Multatuli hospital, Medan. The aim of this research is to test the performance of BmT and its effectiveness in treating patients with neurological disorders. In this case, the nervous disorders experienced by the patient are mild/severe strokes, pinched nerves, and weak nerves. The BmT is an instrument equipped with four main components, namely the Galvanic Skin Response (GSR) sensor to detect stress levels, the MPX5050dp sensor to detect Beat Per Minute (bpm). Memory card as a storage medium for 16 instrumental music works and songs created by composer Prof. Junita Batubara, S.Sn., M.Sn and headphones as a medium for listening to music. Through the use of quasi-experimental methods, the results of this study show that out of 22 (twenty two) outpatients in the neurology unit at Matha Friska Hospital in Medan, the patients experienced a decrease in GSR and BPM numbers based on the results of the numbers that appeared on the BmT monitor screen before and after being given music therapy treatment. Furthermore, researchers also obtained information that the patient experienced a feeling of relaxation, which eased the pain in the patient's limbs both during the process and after music therapy.